Design of code switching and code-mixing game in Sundanese Wewengkon Kuningan language with ethnolinguistic content - Jaelani, Asep Jejen; Hikmat, Ade; Safi’i, Imam (Universitas Muhammadiyah Malang, 2024)
Sundanese language in the Kuningan region. The development of sociolinguistic games is essential because it can increase understanding and awareness of linguistic and cultural diversity among players, especially among children and adolescents, including college students. This game serves as an engaging educational tool for learning sociolinguistic aspects, such as dialect variations and language interactions in a fun and interactive context. In addition, sociolinguistic games support the preservation of local languages and cultures in a modern and accessible way. In this game design research, researchers refer to the MDA (Mechanics, Dynamics, Aesthetics) framework to understand and design the gaming experience. Mechanics refers to the rules and systems of the game, Dynamics describes the player’s interaction with the system, and Aesthetics includes the emotional experience of the player. This framework helps designers create rich and satisfying experiences by considering the interaction of these elements. The game is evaluated using the LORI (Learning Object Review Instrument) instrument to assess its pedagogical qualities, involving assessments from experts and users. The findings point to the need for RPG game designs that support language and ethnolinguistic elements, focusing on code switching and code mixing in the context of Sundanese society. The results of the evaluation show that this game not only contributes to the understanding of sociolinguistic concepts but also fosters a positive attitude towards Indonesian and Sundanese culture.